Improving Students Speaking Ability through Picture at Junior High School - Yasin, Moh. Ilham; Fikri, Moh. Hilman; Sudrajad, Wahyu; Syakur, Abd.; Partini; Gigih Dwi Ananto; Iman Jauhari (Universitas Kristen Cipta Wacana, 2024)
English plays an important role as international language among other languages. Speaking as one of important English skills is considered important to be taught. Speaking is skill that taught with other language skills. In fact, speaking is not an easy skill to be mastered. Most of junior high school students are unable to speak English well. One of alternative to help teacher to create natural communication is by using picture. The design of this research is classroom action research (CAR) which aims at solving problem experienced by classroom teacher to increase the students’ speaking ability by using describing as technique (Aqib 2006), as cited in research Clark (1972). This research has done in two cycles. The objective of this study is to describe how wholesome describing picture can improve speaking ability of seventh grade students in SMP Wahid Hasyim Malang. The researcher hopes that the result of this study useful either theoretically and practically to motivate students and teacher creative in learning process especially in speaking class. the teaching and learning process becomes much better. Before implementing picture technique the students have low self-esteem, fear of making mistakes, shyness and lack of motivation. After implementing the technique they feel confident, did not shy again, and talk with high voice. It also brings good impact on increasing the learning process and they can work as a group. The result on language function showed that in describing picture they speak with occasional hesitation, use adequate vocabulary, use comprehensible pronunciation, and use complex sentence in asking responding.